2020
DOI: 10.3390/jcm9030719
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Eye Assessment in Psoriatic Arthritis Patients sine-Psoriasis: Evidence for a Potential Association with Systemic Inflammation

Abstract: Background: Ocular involvement in Psoriatic Arthritis (PsA) patients is mainly associated with uveitis but there remains a paucity of data on dry eye and retinal abnormalities. We aimed to analyze dry eye and subclinical retinal abnormalities in a cohort of PsA patients sine-psoriasis (PsO). Methods: PsA patients sine-PsO were enrolled. Best-corrected-visual-acuity, ocular-surface-disease-index (OSDI), Schirmer test, tear film breakup-time, standard-automated-perimetry (SAP, mean deviation—MD, pattern standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…Of the 15 studies, four studies reported data on the prevalence of dry eye disease [14, 30, 33, 35]. According to the data from 555 people (303 psoriasis patients and 252 non-psoriasis controls), psoriasis patients showed a significantly higher prevalence of dry eye disease than the non-psoriasis controls (OR, 8.49, 95% CI, 3.34–21.58, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 studies, four studies reported data on the prevalence of dry eye disease [14, 30, 33, 35]. According to the data from 555 people (303 psoriasis patients and 252 non-psoriasis controls), psoriasis patients showed a significantly higher prevalence of dry eye disease than the non-psoriasis controls (OR, 8.49, 95% CI, 3.34–21.58, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…111 As with AS, anterior uveitis is the most frequent manifestation in PsA, occurring in 2–25% of cases. 112 The presence of DED in patients with PsA is mainly associated with the occurrence of concomitant PsO. However, a recent study by Chimenti et al described a significantly higher prevalence of DED, defined as a Schirmer test < 5 mm and/or a TBUT <10 s, in PsA patients without PsO compared with healthy controls.…”
Section: Dry Eye Disease and Associated Ocular Complications With Sys...mentioning
confidence: 96%
“…Eye changes in patients with psoriasis are considered to be a consequence of systemic inflammation (7) and increased cytokine production; however, they are often overlooked, although their progression may result in visual impairment. Changes in the tear film, the conjunctival surface, or disruption of the meibomian glands are common among patients with psoriasis.…”
Section: Etiopathogenesismentioning
confidence: 99%